(untitled) (Journal of Applied Oral Science, 2010)
OBJECTIVE: This study assessed and compared the immunoexpression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) in radicular cysts (RCs) and residual radicular cysts (RRCs), relating them to the angiogenic index and the intensity of the inflammatory infiltrate. MATERIAL AND METHODS: Twenty RCs and 10 RRCs were evaluated by immunohistochemistry using anti-VEGF and anti-MMP-9 antibodies. The angiogenic index was determined by microvessel count (MVC) using anti-von Willebrand factor antibody. RESULTS: The expression of both VEGF and MMP-9 was higher in RCs than in RRCs. RCs and RRCs presented strong epithelial expression of VEGF, irrespective of the intensity of the inflammatory infiltrate. Lesions with strong expression of MMP-9 showed significantly higher number of immunopositive cells for VEGF (p